2002
DOI: 10.1093/humrep/17.6.1591
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid and serum concentrations of myo-inositol in patients undergoing IVF: relationship with oocyte quality

Abstract: We propose that higher concentrations of MI and E(2) in human FF appear to play a role in follicular maturity and provide a marker of good quality oocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
1
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 42 publications
3
90
1
13
Order By: Relevance
“…The concentration of myo-inositol has been determined in FF by enzymatic assays (19), and it was found that the myo-inositol concentration is larger in the FF of good quality oocytes than of low quality ones. However, in the present work, only a weak signal from myo-inositol was detected in the J-resolved spectra, suggesting that it is present at low concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of myo-inositol has been determined in FF by enzymatic assays (19), and it was found that the myo-inositol concentration is larger in the FF of good quality oocytes than of low quality ones. However, in the present work, only a weak signal from myo-inositol was detected in the J-resolved spectra, suggesting that it is present at low concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids (progesterone, 17-oestradiol-b, androstenedione) (13), gonadotropins, prolactin (14) or growth factors (16) have been particularly studied. In addition, the role of myo-inositol in follicular maturity (19) and of N-acylethanolamines, which have been found in human reproductive fluids, has been of particular interest (20). These substances may modulate follicular maturation and ovulation, normal and pathological ovarian function, placental and foetal physiology, lactation, infant physiology and behaviour, and may help to regulate multiple physiological and pathological processes in the reproductive system (20).…”
Section: Introductionmentioning
confidence: 99%
“…MI is present in human follicular fluid, where elevated concentrations appear to play a positive role in follicular maturity and provide a marker of goodquality oocytes [9] . Our study demonstrated that MI oral supplementation restores spontaneous ovulation and menstrual cycles, and increases progesterone secretion in theluteal phase, in most infertile patients with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Foliküler sıvıdaki MI düzeyinin yüksek olması, daha yüksek kalitede bir oosit oluşumu ile korelasyon göster-mektedir. 12 İnositolün oosit kalitesi üzerine etkisini gösteren çalışmalar Tablo 1'de görülmektedir. İntrasitoplazmik sperm enjeksiyonu [intracytoplasmic sperm injection (ICSI)] uygulanan ve olumlu sonuç vermeyen bireylerde MI'nın over fonksiyonu üzerine etkisini değerlendirmek amacıyla yapılan çalışmada, ICSI programına daha önce dâhil edilmiş, ancak başarı elde edilememiş 72 birey iki farklı gruba ayrılmıştır.…”
Section: Ovülasyonunclassified